The Influence of Organizational Support, Personality and Professionalism on Organizational Citizenship Behaviour (OCB) and Police Performance - Earlyanti , Novi; Hamid , Supardi (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this study was to analyze and test the relationship between organizational support and organizational citizenship behavior (OCB), personality and organizational citizenship behavior (OCB), professionalism and organizational citizenship behavior (OCB), and organizational citizenship behavior (OCB) on police performance. This type of research is a quantitative research with a survey method or approach, the respondents of this study were 405 police officers who were determined by the simple random sampling method. Data analysis using the Structural Equation Modeling (SEM) method with SmartPLS 3.0 software will be used in the model and hypothesis testing. Data were obtained by distributing online questionnaires designed with a Likert scale of 1 to 7. The stages of data analysis in this study were validity, reliability and hypothesis testing. and significant to organizational citizenship behavior (OCB), professionalism has a positive and significant effect on organizational citizenship behavior (OCB), organizational citizenship behavior (OCB) has a positive and significant effect on Police Performance.